Role of Chemical Adatoms in Fracture Mechanics of Graphene Nanolayer. (2019) - Verma, Akarsh; Parashar, Avinash; Packirisamy, M.
Abstract: Functionalized graphene's exceptional compatibility and interfacial interaction with host polymer matrix were the motivating features for their fracture description. The authors have considered hydroxyl, epoxide and carboxyl functional groups for this examination; as our main area was to grasp the molecular physics behind their adsorption in graphene lattice. These oxygen variants of graphene form the backbone of intrinsic atomic structure of graphene oxide (GO). Molecular dynamics (MD) simulations in combination with reactive force field (ReaxFF) have been executed to perceive the failure mechanisms in GO framework. Since the literature does not provide an extensively acknowledged model for GO structure, its fracture toughness values are also untold. The authors have tried to correct this gap and forecasted a range of fracture toughness numerical value of 1.6 ± 0.25 MPa m -1/2 by examining their various configurations.